Contralateral Obturator to Femoral Nerve Branch Transfer for Multilevel Lumbosacral Plexus Avulsion Injury. Issue 12 (December 2021) - Nichols, D. Spencer; Chim, Harvey
Abstract : Summary: We report successful restoration of quadriceps function following contralateral obturator to lateral branch of the femoral nerve transfer (with intervening autograft) in two patients with multilevel lumbosacral root avulsions, resulting in severe unilateral motor and sensory deficits. Three years postoperatively, patient 1 had regained Medical Research Council grade 3 knee extension with the ability to extend against 10 pounds of resistance. At 28 months postoperatively, patient 2 had regained Medical Research Council grade 2 knee extension. Treatment options for severe lumbosacral plexus injuries with multiple root avulsions are limited. This approach offers a new option for these devastating injuries.